Design B-Series propeller of traditional fishing vessel - Zulhilmi, Shafie (2012)
This thesis presents a study on determination of an optimum parameter in designing fishing vessel propeller. The right combination between the propeller design and the engine is required to give better performance and fuel economy. The objective of this project is to find the diameter pitch of the propeller and the blade dimensional characteristic. By referring to the ‘Wageningen B-series’ tables and data collection, the study has been carried out. From the data, the optimum diameter pitches of the propeller are calculated. As a result, an optimum designed of the propeller which could give high efficiency, high performance and reduced the fuel consumption of the fishing vessel is produce.